Incidence differences between first primary cancers and second primary cancers following skin squamous cell Carcinoma as etiological clues - Zheng, Guoqiao; Sundquist, Kristina; Sundquist, Jan; Försti, Asta; Hemminki, Akseli; Hemminki, Kari (Clinical epidemiology, 2020)
Background: Most literature on second primary cancers (SPCs) focuses on possible factors, which may increase the risk of these cancers, and little attention has been paid for the overall incidence differences between first primary cancers (FPCs) and same SPCs. We wanted to compare the incidence rates for all common cancers when these were diagnosed as FPCs and SPCs after invasive and in situ squamous cell carcinoma (SCC) of the skin, which are usually treated by surgery only. - Methods: Cancers were identified from the Swedish Cancer Registry from the years 1990 through to 2015, and they included, in addition to skin cancers, 20 male cancers totaling 484,850 patients and 22 female cancers totaling 452,909 patients. Standardized incidence rates and relative risks (RRs) were calculated for sex-specific common cancers as FPC and as SPC after skin SCC. Spearman rank correlations were used in the analysis of incidence ranking of FPC and SPC. - Results: Of total, 29,061 men and 23,533 women developed invasive SCC and 27,842 men and 36,383 women in situ SCC. The total number of 20 other male cancers was 484,850 and of 22 female cancers it was 452,909. Rank correlations ranged from 0.90 to 0.96 (P~5×10-6), indicating that overall skin SCC did not interfere with SPC formation. The exceptions were increased SPC risks for melanoma, sharing risk factors with skin SCC, and non-Hodgkin and Hodgkin lymphoma, and cancers of the upper aerodigestive tract, connective tissue, and male and female genitals suggesting contribution by skin cancer initiated immune dysfunction. - Conclusion: The incidence ranking of SPCs after skin cancers largely follows the incidence ranking of FPCs indicating that overall skin SCC does not greatly interfere with the intrinsic carcinogenic process. The main deviations in incidence between FPC and SPC appeared to be due to shared risk factors or immunological processes promoting immune responsive cancer types.
Gesehen am 13.10.2020